Trip Attraction Rates of Banking Services in Developing Countries' Cities - Metwally G. M. Altaher; Mohamed A. Elsayed; Hassan D. Hassanin; Ali R. Ibrahim (Civil Engineering Journal, 2023)
There is a lack of studies on trip generation rates related to land use activities in developing countries. The absence of trip rates makes transportation planners use rates listed in the Institute of Transportation Engineers (ITE) Trip Generation Manual, which may lead to unrealistic results. The study aims to determine trip attraction rates for banking services in Zagazig city, Egypt, and evaluate the factors affecting the attracted trips to the banks. The study has designed and implemented a comprehensive data collection and analysis program. The study sample contained nine banks. The study has conducted field surveys that counted the total number of persons entering/exiting the bank under investigation and the generated traffic volume of the adjacent street. The trip rates have been established in terms of independent variables, i.e., gross floor area, the total number of employees, and the number of tellers for different types of banks. Findings showed that average trip attraction rates for public banks were higher than for private banks. There was a strong relationship between trip attractions and the total number of employees at public banks. The most representative factor of private banks' trip attractions was the number of tellers. Doi: 10.28991/CEJ-2023-09-02-07 Full Text: PDF